Glycoprotein B7-H3 overexpression and aberrant glycosylation in oral cancer and immune response - Chen, Jung-Tsu; Chen, Chein-Hung; Ku, Ko-Li; Hsiao, Michael; Chiang, Chun-Pin; Hsu, Tsui-Ling; Chen, Min-Huey; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2015)
The incidence and mortality rate of oral cancer continue to rise, partly due to the lack of effective early diagnosis and increasing environmental exposure to cancer-causing agents. To identify new markers for oral cancer, we used a sialylation probe to investigate the glycoproteins differentially expressed on oral cancer cells. Of the glycoproteins identified, B7 Homolog 3 (B7-H3) was significantly overexpressed in oral squamous cell carcinoma (OSCC), and its overexpression correlated with larger tumor size, advanced clinical stage, and low survival rate in OSCC patients. In addition, knockdown of B7-H3 suppressed tumor cell proliferation, and restoration of B7-H3 expression enhanced tumor growth. It was also found that the N-glycans of B7-H3 from Ca9-22 oral cancer cells contain the terminal α-galactose and are more diverse with higher fucosylation and better interaction with DC-SIGN [DC-specific intercellular adhesion molecule-3 (ICAM-3)–grabbing nonintegrin] and Langerin on immune cells than that from normal cells, suggesting that the glycans on B7-H3 may also play an important role in the disease.